Information systems security policies : a survey in portuguese public administration - Lopes, Isabel Maria (2010)
Information Systems Security is a relevant factor for present organizations. Among the security measures, policies assume a central role in literature. However, there is a reduced number of empirical studies about the adoption of information systems security policies. This paper contributes to mitigate this flaw by presenting the results of a survey in the adoption of Information System Security Policies in Local Public Administration in Portugal. The results are discussed in light of literature and future works are identified with the aim of enabling the adoption of security policies in Public Administration.